Conformation and dynamics of melittin bound to magnetically oriented lipid bilayers by solid-state (31)P and (13)C NMR spectroscopy. - Naito, A (2000)
The conformation and dynamics of melittin bound to the dimyristoylphosphatidylcholine (DMPC) bilayer and the magnetic orientation in the lipid bilayer systems were investigated by solid-state (31)P and (13)C NMR spectroscopy. Using (31)P NMR, it was found that melittin-lipid bilayers form magnetically oriented elongated vesicles with the long axis parallel to the magnetic field above the liquid crystalline-gel phase transition temperature (T(m) = 24 degrees C). The conformation, orientation, and dynamics of melittin bound to the membrane were further determined by using this magnetically oriented lipid bilayer system. For this purpose, the (13)C NMR spectra of site-specifically (13)C-labeled melittin bound to the membrane in the static, fast magic angle spinning (MAS) and slow MAS conditions were measured. Subsequently, we analyzed the (13)C chemical shift tensors of carbonyl carbons in the peptide backbone under the conditions where they form an alpha-helix and reorient rapidly about the average helical axis. Finally, it was found that melittin adopts a transmembrane alpha-helix whose average axis is parallel to the bilayer normal. The kink angle between the N- and C-terminal helical rods of melittin in the lipid bilayer is approximately 140 degrees or approximately 160 degrees, which is larger than the value of 120 degrees determined by x-ray diffraction studies. Pore formation was clearly observed below the T(m) in the initial stage of lysis by microscope. This is considered to be caused by the association of melittin molecules in the lipid bilayer.